PREPARATION OF REFLECTIVE PEDAGOGY PARADIGM LEARNING FOR THE LECTURERS BASED ON COMPUTATIONAL CHEMISTRY - Yuliyanto, Eko; Hidayah, Fitria Fatichatul; Istyastono, Enade Perdana; Wijoyo, Yosef; Hartayu, Titien Siwi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The study aims to prepare lecturers on reflective pedagogy paradigm (RPP). This research was a mixed method. It was conducted with nine students and a model lecturer (mantee) who underwent mentoring. It was held in 4 meetings and observed by two observers. The assessment was conducted using data triangulation to a model lecturer based on video recording, reflection by mantee and students. The measure of process success was based on video recordings by ≥70%. The lecturer’s reflection to demonstrate the readiness in the teaching, and the student’s reflection is ≥ 60%. The results of mantee and student at every stage are: 81%, 69%, 88%, and 50%; 72%, 92%, 73%, and 85% of context, experience, reflection, and action. The results of the evaluation there was a significant difference before and after the learning based on RPP (p = 0.035). So, mentees was able to manage RPP and able to make students active to learn from theory to practice.